Efficacy of a potassium-competitive acid blocker for improving symptoms in patients with reflux esophagitis, non-erosive reflux disease, and functional dyspepsia - Asaoka, Daisuke (Biomed Rep, 2017)
The aim of the present study was to investigate the efficacy of a potassium-competitive acid blocker (PCAB) named vonoprazan (VPZ) for improving symptoms in patients with reflux esophagitis (RE), non-erosive reflux disease (NERD), and functional dyspepsia (FD). A hospital-based, retrospective study of outpatients in our department (Department of Gastroenterology, University of Juntendo, Tokyo, Japan) between March 2015 and August 2016 was performed. The patients who were experiencing heartburn, acid regurgitation, gastric pain, and/or a heavy feeling in the stomach of at least moderate severity at baseline were treated with 20 mg VPZ once daily for 4 weeks. The patients completed the global overall symptom (GOS) scale to determine their symptom severity at baseline and after the 4 week treatment period. The proportions of patients with RE, NERD, and FD achieving improvement of their symptoms, defined as a GOS scale score of 1 (‘no problem’) or 2 (‘minimal problem’), were evaluated. During 4 weeks of VPZ therapy, changes in the gastroesophageal reflux disease (GERD) score, which was defined as the total points for heartburn and acid regurgitation on the GOS scale in patients with RE and NERD, and in the FD score, which was defined as the total points for gastric pain and a heavy feeling in the stomach on the GOS scale in patients with FD, were also evaluated. A total of 88 eligible cases were included in the present study, comprising 20 patients with RE, 25 patients with NERD, and 43 patients with FD. The rates of symptomatic improvement in patients with RE, NERD, and FD were 75.0, 60.0, and 48.8%, respectively. For the patients who were first administered VPZ, the rates of symptomatic improvement were 90.9, 66.7, and 58.8% in patients with RE, NERD, and FD, respectively. For those patients who were resistant to 8 weeks of proton pump inhibitor therapy, the rates of symptomatic improvement were 55.6, 53.8, and 42.3% in patients with RE, NERD, and FD, respectively. The GERD score in patients with RE and NERD, and the FD score in FD patients, were decreased after 4 weeks of VPZ therapy (P<0.01). In patients with RE, NERD and FD, the possibility that PCAB may be used as a novel therapeutic drug was suggested. However, the number of study subjects was small; therefore, further, larger and prospective studies are required.